Pembrolizumab: Role of Modeling and Simulation in Bringing a Novel Immunotherapy to Patients With Melanoma. (5th November 2016) - de Greef, R; Elassaiss‐Schaap, J; Chatterjee, M; Turner, DC; Ahamadi, M; Forman, M; Cutler, D; de Alwis, DP; Kondic, A; Stone, J
Abstract : Recently, immunotherapy has yielded promising results in several cancer types. Contrary to the established classical chemotherapy‐dosing paradigm, a maximum tolerated dose approach does not always produce better clinical outcomes for novel targeted therapies, as their efficacy is frequently robust at pharmacologically active doses below the maximum tolerated dose. Integrated safety and efficacy assessments are needed to inform clinical dose and trial design, and to support an early identification of potentially safe and efficacious combination treatments.